(untitled) (Scientific journal of the Fergana State University, 2024)
The conducted research allowed us to establish that in gymnastics, elements in different shells have different levels of threadness. Consequently, their effect on the body of young gymnasts, in particular on the cardiovascular system, is not the same. Therefore, when planning training loads, it is necessary to take into account the complexity of the elements for each type of multi-sport and their impact on the body of adolescents.